Does the Combination of Nebulizer and Guided Imagery Therapy Affect the Frequency of Breathing in Patients with Asmatic Status? - Padila Padila; Juli Andri; Andry Sartika; Muhammad Bagus Andrianto (Jurnal Keperawatan Silampari, 2024)
This research aims to determine whether the combination of nebulizer therapy and guided imagery affects respiratory frequency in patients with asthmatic status. The research design used in this study was Queasy Experimental in one intervention group. The results of the study showed that p-value = 0.02, with 0.02 < 0.05 meaning that there was an effect of the combination of nebulizer therapy and guided imagery on reducing the respiratory frequency in patients with asthmatic status in the emergency room at M. Yunus Hospital, Bengkulu City. In conclusion, a combination of nebulizer therapy and guided imagery reduces respiratory frequency in patients with asthmatic status in the emergency room at M. Yunus Hospital, Bengkulu City. Keywords: Guided Imagery, Nebulizer, Respiratory Frequency, Asthmatic Status